The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1128/jb.01168-12
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Component Sensor KinB Acts as a Phosphatase To Regulate Pseudomonas aeruginosa Virulence

Abstract: dPseudomonas aeruginosa is an opportunistic pathogen that is capable of causing both acute and chronic infections. P. aeruginosa virulence is subject to sophisticated regulatory control by two-component systems that enable it to sense and respond to environmental stimuli. We recently reported that the two-component sensor KinB regulates virulence in acute P. aeruginosa infection. Furthermore, it regulates acute-virulence-associated phenotypes such as pyocyanin production, elastase production, and motility in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Intriguingly, zebrafish studies suggested that neither the kinase activity of kinB nor its canonical partner, algB , were required for acute virulence (Chand et al, 2011), but that the phosphatase activity of KinB was critical (Chand et al, 2012). To investigate the role of kinB in LK, we first carried out a time course study to confirm that PA14 ΔkinB was attenuated in both LK (Figure S2E) and SK (Figure S2F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, zebrafish studies suggested that neither the kinase activity of kinB nor its canonical partner, algB , were required for acute virulence (Chand et al, 2011), but that the phosphatase activity of KinB was critical (Chand et al, 2012). To investigate the role of kinB in LK, we first carried out a time course study to confirm that PA14 ΔkinB was attenuated in both LK (Figure S2E) and SK (Figure S2F).…”
Section: Resultsmentioning
confidence: 99%
“…KinB’s role in alginate production, however, does not appear to be relevant for LK. Alginate is more commonly involved in chronic infections and is not thought to be necessary for acute virulence (Yorgey et al, 2001), and a recent report suggests that KinB may be key in mediating the transition between acute and chronic P. aeruginosa infections (Chand et al, 2012). Also, it is unlikely that KinB plays a major role in regulating pyoverdin production in LK since kinB mutants synthesize normal levels of pyoverdin ( data not shown ).…”
Section: Discussionmentioning
confidence: 99%
“…Virulence in this assay involves at least two independent determinants: the phosphatase activity of the kinB gene of P. aeruginosa (10, 17) and production of the bacterial siderophore pyoverdine (10, 18). In brief, 20 young adult C. elegans worms are added to each well of a 384-well plate containing P. aeruginosa and incubated at 25°C for approximately 36 to 40 h. Bacteria were washed away, and dead worms were stained with a membrane-impermeable dye.…”
Section: Resultsmentioning
confidence: 99%
“…This may allow KinB‐AlgB to act as global regulator controlling the switch from an acute virulence phenotype (motile, pyocyanin and elastase‐producing) with AlgB un‐phosphorylated, to a chronic virulence phenotype (non‐motile, alginate‐producing) with AlgB phosphorylated. Furthermore, the phosphorylation of AlgB is not dependent on KinB and its phosphorylation may be via unknown alternative sensor kinases (Chand et al ., 2011; 2012). To further complicate this situation, it has recently been shown that KinB‐AlgB may play a role in the AlgW‐mediated degradation of the MucA anti‐sigma factor, although the mechanisms remain unclear (Damron et al ., ) (Fig.…”
Section: Transcriptional Regulationmentioning
confidence: 99%